2003
DOI: 10.1002/hfm.10048
|View full text |Cite
|
Sign up to set email alerts
|

Chinese perceptions of implied hazard for signal words and surround shapes

Abstract: With the increase of international trade and communications, the issue-whether people in different cultures similarly interpret and understand the extent implied by signal words and their associated panels in warning design-is getting more and more interesting and important. Two experiments were conducted to collect data on perception of arousal strength of signal words and surround shapes of the Chinese population and to determine whether those findings for Chinese are validated for Americans. A total of 120 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 13 publications
4
24
0
Order By: Relevance
“…The ten warning signal words used in this study were selected from a previous study (Yu et al 2004). Each word consisted of two Chinese characters.…”
Section: Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…The ten warning signal words used in this study were selected from a previous study (Yu et al 2004). Each word consisted of two Chinese characters.…”
Section: Stimulimentioning
confidence: 99%
“…In addition, the general dimension "arousal strength" has been proposed. In a recent study by Yu et al (2004), participants were required to rate the arousal level of 16 warning signal words. They found that the arousal level of these words could be divided into three hazard levels-high level, moderate level and low level.…”
Section: Introductionmentioning
confidence: 99%
“…Yu, Chan and Salvendy reported an experiment with Chinese safety words for determining the level of stimulus generation among Chinese workers [12]. The results indicated that words could imply different levels of hazard.…”
Section: Literature Surveymentioning
confidence: 99%
“…The more a priori perception of hazard, the more likely people will look for and read warnings and comply by taking precautions [9]. Hazard rating among diverse populations depends on factors such as gender, age, social status, culture and country [9,10,11,12]. Safety concerns among individuals are universal but priority given to safety or safety-related decisionmaking may vary among or within countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation